A Study on the Utilization of Mobile Electronic Notice Service using Korean Digital Identity Guidelines - Jong-Bae Kim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently, due to the spread of infectious diseases, the demand for services in a non-connected environment is increasing worldwide. Identifying the service counterpart in such a non-face-to-face environment has become the most important task. In this paper, we examine the status of overseas personal identification systems and explain the Korean digital identity guideline. Using the Korean digital identity guideline, it presents the application plan of mobile electronic notification service that has delivery and proof effect. For personal digital identity, Korea identifies citizens based on a registration number (RN) that is uniquely assigned at birth. However, if the RN is leaked or exposed, the problem of personal privacy invasion has emerged, and in the end, due to personal information protection issues, RNs cannot be collected unless required by law. Therefore, connecting information (CI) was utilized as a digital identity capable alternative to RN to clearly identify users online.CI has the advantage of being encrypted as a 1:1 match to the RN and not being able to identify an individual even if leaked. The mobile electronic notification service is designed to accurately deliver information to the target person in a non-face-to-face environment using CI. This service uses CI to identify the recipient of the electronic document, and after receiving identification from the personal identity proofing agency (PIPA), the service can be verified by reading the information. In this paper, we propose a method to easily provide information in the non-face-to-face era by presenting a method to apply to mobile electronic notification service (MENS) using Korean user identification guidelines. Through the proposed method, it can be confirmed that a system can be established to facilitate the mobile electronic notification service, which has the same effect as the delivery of information online and offline in the non-face-to-face era.